Southside Retrace: Strategies to Retain, Redefine, and Reconnect Public Housing in South Omaha - Corrie, Brian; Sun, Wei; Sundine, Josh; Depriest, Anthony; Nelson, Bre; Brown, Skylar; Rankin, Rachel; Lemken, Andrea; Nyp, Chandler; Finck, Caroline; Lanning, Evan; Wong, Astrid (Kansas State University. College of Architecture, Planning & Design, Department of Landscape Architecture and Regional & Community Planning, 2016)
The Omaha Housing Authority (OHA) is at a critical crossroad. Southside Terrace public housing infrastructure has exceeded its functional lifespan and needs to be replaced. The cost to maintain the 75-year-old residential buildings is no longer viable for OHA, which intends to demolish the site and rebuild. OHA has applied for a HUD Choice Neighborhood Planning Grant and envisions rebuilding the community to better serve its 1,300 residents, roughly half of whom are Sudanese or Somali refugees. Transitioning to new facilities is highly complex, time sensitive, and will have profound effects on the lives of the residents, neighbors, and service providers. Southside Retrace presents research, analysis, critical mapping, and four planning and design proposals for the future of Southside Terrace, ranging from immediate low-impact design to visionary planning strategies for the future. Twelve Kansas State University mid-level landscape architecture graduate students completed the work during the summer of 2016 in an intensive 8-week Community Planning and Design studio. The course was co-led by Associate Professor Blake Belanger and Associate Professor Howard Hahn. We identified three vital considerations in redeveloping the community: retaining vulnerable populations within close proximity of needed community services during and after construction; redefining quality of life and housing for residents and newcomers; and reconnecting the new community with the surrounding neighborhood. To address these wicked problems, the studio used a mixed-method, evidence-based design approach for research and planning. Students researched historical, ecological, demographic, social, and economic variables at the regional, metro, and local scale through mapping and review of literature. The professors assigned seminar readings and led discussions about public housing and the dynamics of urban poverty, urban design, community planning, safety, landscape architecture, and critical mapping to provide a theoretical foundation for the studio work. Faculty administered a resident survey, and together with students led a focused partner workshop followed by a public resident workshop. During the first site visit, students spent time walking the community and speaking with project partners about their concerns and aspirations. Students rigorously analyzed the site and context using critical mapping, an iterative research and design process that identifies opportunities, dilemmas, and preliminary design strategies. Working in teams of three, the students applied research and analysis findings to develop planning/design proposals to retain vulnerable populations close to services, redefine the quality of life for residents, and reconnect the community to the neighborhood. The critical maps, documented in the book’s appendix, provide findings on a wide variety of research questions. Particularly important findings include: (1) Omaha’s highest concentration of social support service providers is located near Southside Terrace; (2) residents are vulnerable to violence and accidents due to unsafe environmental and infrastructural conditions in and around the community; (3) steep slopes presents technical challenges to redevelopment, especially if the site boundary does not expand; and (4) public housing precedents suggest land use, public space design, street design, and building organization should be reconsidered. Each of the four studio proposals presents a different approach to redevelopment, based upon geographic areas of redevelopment, topographic manipulation, phasing strategies, and time horizon. Three of the proposals follow a traditional master planning model, with detailed site plans including park and civic space design, street layout, building footprints, vehicle parking areas, and ecological planning. The fourth proposal, Southside Catalyst, studies a larger geographic area and looks further into the future. Acknowledging that longer time horizons usually involve greater uncertainty, Southside Catalyst presents a bold vision of long-range potential for the district, and an adaptive strategy for the Southside Terrace site itself. All proposals consider strategic phasing to accommodate the existing residents in different ways. Some proposals expand beyond the existing site boundary to suggest potential for partnerships with nearby institutions and property owners. We hope our research, planning, and design will help inspire a bright future for residents, the neighborhood, and the region. The effort was supported with funding from Kansas State University’s Technical Assistance to Brownfields.
Keywords: Public Housing; South Omaha; Topographic Manipulation; Phasing Strategies; Time Horizon; Southside Terrace